Perception of the Importance of Inherited Genetics and Lifestyle on the Development of Chronic Diseases: A UK Cross‐Sectional Survey - Aamir Hussain; Lourdes Santos‐Merx; Mariasole Da Boit (Health Science Reports)
ABSTRACT Background and Aims There is emerging evidence that genes, lifestyles and environment play a prominent role in the development of non‐communicable diseases. Currently, there is not information on people's perception of inherited genetics vs. lifestyle on disease development. Knowing people's belief on disease etiology will better inform public health strategies for the adoption of a healthy lifestyle. Methods Individuals aged 18 years and over were recruited in 2019 among the UK population and 363 participants completed an anonymous questionnaire. The main outcomes assessed were perception of importance of inherited genes and lifestyle on the development of diseases. T‐tests and χ2 were used. Results The score for the importance of inherited genes in disease development was significantly lower than the lifestyle score (7.5 ± 1.7 vs. 8.5 ± 1, p <0.001). Moreover, the majority of the respondents chose lifestyle over inherited genes as most important factor for cancer, cardiovascular disease and Type 2 Diabetes development (50.8% vs. 29.6%, 79% vs. 11.9%, 85.7% vs. 9.6%; respectively), while 60.6% of respondents selected inherited genes for rheumatoid arthritis (p < 0.05). Knowledge about genes or a healthy lifestyle did not influence the selection of lifestyle as the most important factor (p > 0.05). Conclusion Overall, participants were well aware of the importance of lifestyle as a determinant risk factor for chronic disease development. This is an important step toward adopting a healthy lifestyle.